Characterization of antiseizure medications effects on the EEG neurodynamic by fractal dimension - Porcaro, Camillo; Seppi, Dario; Pellegrino, Giovanni; Dainese, Filippo; Kassabian, Benedetta; Pellegrino, Luciano; De Nardi, Gianluigi; Grego, Alberto; Corbetta, Maurizio; Ferreri, Florinda (Frontiers in Neuroscience, 2024)
Objectives: An important challenge in epilepsy is to define biomarkers of response to treatment. Many electroencephalography (EEG) methods and indices have been developed mainly using linear methods, e.g., spectral power and individual alpha frequency peak (IAF). However, brain activity is complex and non-linear, hence there is a need to explore EEG neurodynamics using nonlinear approaches. Here, we use the Fractal Dimension (FD), a measure of whole brain signal complexity, to measure the response to anti-seizure therapy in patients with Focal Epilepsy (FE) and compare it with linear methods.Materials: Twenty-five drug-responder (DR) patients with focal epilepsy were studied before (t1, named DR-t1) and after (t2, named DR-t2) the introduction of the anti-seizure medications (ASMs). DR-t1 and DR-t2 EEG results were compared against forty age-matched healthy controls (HC).Methods: EEG data were investigated from two different angles: frequency domain -spectral properties in δ, θ, α, β, and γ bands and the IAF peak, and time-domain -FD as a signature of the nonlinear complexity of the EEG signals. Those features were compared among the three groups.The δ power differed between DR patients pre and post-ASM and HC (DR-t1 vs. HC, p<0.01 and DR-t2 vs. HC, p<0.01). The θ power differed between DR-t1 and DR-t2 (p=0.015) and between DR-t1 and HC (p=0.01). The α power, similar to the δ, differed between DR patients pre and post-ASM and HC (DR-t1 vs. HC, p<0.01 and DR-t2 vs. HC, p<0.01). The IAF value was lower for DR-t1 than DR-t2 (p=0.048) and HC (p=0.042). The FD value was lower in DR-t1 than in DR-t2 (p=0.015) and HC (p=0.011). Finally, Bayes Factor analysis showed that FD was 195 times more likely to separate DR-t1 from DR-t2 than IAF and 231 times than θ.Discussion: FD measured in baseline EEG signals is a non-linear brain measure of complexity more sensitive than EEG power or IAF in detecting a response to ASMs. This likely reflects the non-oscillatory nature of neural activity, which FD better describes.Our work suggests that FD is a promising measure to monitor the response to ASMs in FE.